Hard debt, soft CEO and union rents (University of Oxford, 2003)
Sometimes shareholders are better off delegating to a CEO with different objectives than their own. A top manager motivated to share surpluses with workers can encourage union members to adopt efficient production methods. Bond covenants may constrain managers from acquiescing to union wage demands. Nevertheless, we argue that unions can win higher wages by altering the non-shirking constraint. Resistance to monitoring leads to deadweight losses that a â€